Diosgenin alleviates D-galactose-induced oxidative stress in rats’ brain and liver targeting aging and apoptotic marker genes - El-Far, Ali H.; Elghaity, Mona M.; Mohamed, Shymaa A.; Noreldin, Ahmed E.; Elewa, Yaser H. A.; Al Jaouni, Soad Khalil; Alsenosy, Abdelwahab A. (Frontiers in Molecular Biosciences, 2024)
The theory of aging is primarily concerned with oxidative stress caused by an imbalance in reactive oxygen species generation and cellular antioxidants. To alleviate the oxidative stress, we investigated the protective effect of diosgenin (DSG) for D-galactose (D-gal) using 20 and 40 mg of DSG/kg/day/orally for 42 days. The findings showed that D-gal caused brain and liver oxidative injuries by upregulating aging and oxidative markers. To counteract the oxidative stress caused by D-gal, DSG upregulated glutathione peroxidase-1, superoxide dismutase-1, and glutathione Stransferase-α. DSG also diminished the expression of p53, p21, Bcl-2-associated X protein, caspase-3, and mammalian target of rapamycin in brain and liver, as well as the build-up of βgalactosidase. DSG, in a dose-dependent manner, decreased the oxidative aging effects of D-gal in brain and liver tissues through targeting of aging and apoptotic marker genes. Finally, it should be noted that consuming DSG supplements is a suggesting natural preventative agent that may counteract aging and preserve health through improvement of body antioxidant status and control aging associated inflammation and cellular apoptosis.